2014
DOI: 10.1016/j.mbs.2014.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Central regulation of heart rate and the appearance of respiratory sinus arrhythmia: New insights from mathematical modeling

Abstract: A minimal model for the neural control of heart rate (HR) has been developed with the aim of better understanding respiratory sinus arrhythmia (RSA) – a modulation of HR at the frequency of breathing. This model consists of two differential equations and is integrated into a previously-published model of gas exchange. The heart period is assumed to be affected primarily by the parasympathetic signal, with the sympathetic signal taken as a parameter in the model. We include the baroreflex, mechanical stretch-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 66 publications
4
53
1
Order By: Relevance
“…However, the function of this physiological phenomenon is yet to be fully established. The proposed benefits of RSA include stabilisation of blood pressure, optimisation of cardiopulmonary gas exchange and increased cardiac energy efficiency (Hayano et al 1996;Giardino et al 2003;Elstad, 2012;Ben-Tal et al 2014). Any one of these would assist patients with heart failure where myocardial function and energy are suboptimal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the function of this physiological phenomenon is yet to be fully established. The proposed benefits of RSA include stabilisation of blood pressure, optimisation of cardiopulmonary gas exchange and increased cardiac energy efficiency (Hayano et al 1996;Giardino et al 2003;Elstad, 2012;Ben-Tal et al 2014). Any one of these would assist patients with heart failure where myocardial function and energy are suboptimal.…”
Section: Discussionmentioning
confidence: 99%
“…However, this theory is contentious (Sin et al 2010) and a recent mathematical modelling study could not validate this finding (Ben-Tal et al 2012). Instead, Ben-Tal and colleagues proposed that RSA reduced cardiac work while maintaining physiological levels of arterial carbon dioxide (Ben-Tal et al 2014). We suggest that through these mechanisms RSA serves to optimize oxygen delivery to the heart with increasing workload (Elstad et al 2018).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…RSA -being mediated predominantly by the parasympathetic nervous system -is widely accepted as an indicator of the healthy cardiovascular control at rest (Grossman and Taylor 2007, Larsen et al 2010, Ben-Tal et al 2014. A decrease of RSA magnitude is associated with many pathological states, including myocardial infarction (Fei et al 1996a), and chronic heart failure (Fei et al 1996b) but it decreases also during challenges leading to a decreased parasympathetic and/or increased sympathetic activity (Allen and Crowell 1989, Herbert et al 2010, Mortola et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we built a mathematical model to understand the functional role of RSA and to address the inconsistencies of previous reports (Ben‐Tal et al . , ). We demonstrated that although gas exchange efficiency can improve with both slow and deep breathing, and increased mean heart rate, this was all unrelated to RSA.…”
Section: An Unmet Clinical Needmentioning
confidence: 99%